Ochratoxin A Dietary Exposure of Ten Population Groups in the Czech Republic: Comparison with Data over the World - Ostry, Vladimir; Malir, Frantisek; Dofkova, Marcela; Skarkova, Jarmila; Pfohl-Leszkowicz, Annie; Ruprich, Jiri (Toxins, 2015)
Ochratoxin A is a nephrotoxic and renal carcinogenic mycotoxin and is a common contaminant of various food commodities. Eighty six kinds of foodstuffs (1032 food samples) were collected in 2011-2013. High-performance liquid chromatography with fluorescence detection was used for ochratoxin A determination. Limit of quantification of the method varied between 0.01-0.2 μg/kg depending on the food matrices. The most exposed population is children aged 4-6 years old. Globally for this group, the maximum ochratoxin A dietary exposure for "average consumer" was estimated at 3.3 ng/kg bw/day (lower bound, considering the analytical values below the limit of quantification as 0) and 3.9 ng/kg bw/day (middle bound, considering the analytical values below the limit of quantification as 1/2 limit of quantification). Important sources of exposure for this latter group include grain-based products, confectionery, meat products and fruit juice. The dietary intake for "high consumers" in the group 4-6 years old was estimated from grains and grain-based products at 19.8 ng/kg bw/day (middle bound), from tea at 12.0 ng/kg bw/day (middle bound) and from confectionery at 6.5 ng/kg bw/day (middle bound). For men aged 18-59 years old beer was the main contributor with an intake of 2.60 ng/kg bw/day ("high consumers", middle bound). Tea and grain-based products were identified to be the main contributors for dietary exposure in women aged 18-59 years old. Coffee and wine were identified as a higher contributor of the OTA intake in the population group of women aged 18-59 years old compared to the other population groups.
Keywords: Ochratoxins; jedlá semena; populační skupiny; víno; Coffee; Humans; lidé středního věku; Beer; Czech population; dítě; ochratoxin A; pivo; káva; ovocné a zeleninové šťávy; masné výrobky; Child; Female; mladý dospělý; dospělí; lidé; dietary exposure; exposure sources; ochratoxiny; Wine; Food Microbiology; Edible Grain; předškolní dítě; Adult; food; ženské pohlaví; Male; Middle Aged; kontaminace potravin; Adolescent; Food Contamination; Czech Republic; Young Adult; Meat Products; Česká republika; mužské pohlaví; Child, Preschool; Population Groups; Fruit and Vegetable Juices; mladiství; potravinářská mikrobiologie